Child development : understanding a cultural perspective - Packer, Martin J. (b)
Every child is born into a community, a society with a culture, in which they will live, grow and develop. Cultures lead to differences in children$1 (Bs development, but equally important, culture is an essential component of every child$1 (Bs psychological development.s
Includes references and index.
Keywords: Child development